Issues related to the processing of ferroelectric nanostructures via ex situ and in situ methods - Harada, Scott (Cranfield University, 2008)
This study investigates the impact of several processing parameters on the production of PZT and lead titanate nanostructures, by two different synthesis routes. The first aimed to produce freestanding, nanoscale PZT crystals via a simple, hydrothermal technique. Phase-pure, 52:48 PZT was synthesised within 2 hr at 160 °C in a hydrothermal autoclave. The morphology of the resultant crystals was cubic and micron-sized. Efforts were thus directed at reducing crystal size, by altering several processing conditions. Reaction time and temperature were found to have little effect on crystal size and instead resulted in incomplete reaction below the threshold values shown above. Introducing a 100% excess of Pb precursor led to an improvement in the faceting of the crystals, but again did not lead to a change in average crystal size. However, by using a 2% solution of the surfactant Triton-X, the average crystal size fell from 5 μm to 2 μm. The use of anatase TiO2 in the general hydrothermal procedure imposed a lower limit on the mineraliser concentration that was necessary for dissolution to occur. To overcome this restriction, a hybrid sol-gel/hydrothermal technique was attempted. This had the unexpected result of producing pyramidal microfibres that tapered to nano-sized points. Since the attempts to synthesise freestanding, nanoscale PZT crystals using the hydrothermal method were unsuccessful, work focussed on growing nanoislands on single crystal (100)- SrTiO3 substrates. Heteroepitaxial PZT films up to 1 μm thick, as well as micro- and nanoislands were observed, after extended 24 hr reactions at 160 °C. In some cases, the islands appeared to nucleate along scratches in the SrTiO3 substrate, leading to the formation of microwires up to a millimetre in length. Ferroelectric analysis of the microwires by PFM revealed them to be weakly piezoelectric. The second synthesis route to nanoscale ferroelectrics relied upon the solid phase reaction between Pb and Ti thin films to produce lead titanate. The optimum condition for the crystallisation of the perovskite phase was found to be 1 hr at 650 °C, under an air atmosphere. However, examination of the film morphology revealed large distortions and blistering across the surface. As such, it was not possible to acquire polarisation loop measurements, due to shorting between the top and bottom electrodes. EDAX confirmed that PbO vapour from the film was diffusing into the Si substrate leading to the formation of voids and the production of lead silicate glasses. Alternative adhesion layers for the Pt back electrodes were investigated, in an attempt to limit the diffusion of PbO. Electrical measurements on the films were made possible by substituting Zr for Ti. However, the shape of the hysteresis loops corresponded to a lossy dielectric as opposed to a ferroelectric response from the film. Films annealed on alternative substrates also suffered from blistering, but without the intrusion of PbO. This result suggested that the distortion present in the films was not as a consequence of the interaction between volatile species and the substrate. Instead, blistering and delamination was attributed to stresses generated during the transformation into the PbTiO3 perovskite phase. The solid phase synthesis method was extended to produce PbTiO3 nanoislands by utilising flash thermal evaporations. Deposition times below 1 s resulted in Pb nanoislands with a size range of 5 – 30 nm. Annealing the nanoislands under the same regime as used during the thin film experiments led to the loss of their morphology through melting. To overcome this problem an extended low temperature annealing was adopted. PFM was conducted on various nanoisland and thin film samples produced by the in situ technique. Nanoisland samples subjected to prolonged conventional annealings at 300 °C and brief hot plate annealings at 550 °C exhibited a non-zero piezoresponse. Definitive evidence of ferroelectricity in the nanoisland samples could not be demonstrated, however, as attempts to pole them were unsuccessful. PbTiO3 thin films produced by annealing Pb/Ti bilayers displayed clear c+ and c- ferroelectric domains that were mostly pinned by the grain boundaries. Little evidence of self-polarisation was found, since the average piezoresponse across the image was close to zero. Localised poling resulted in piezoresponse images showing the presence of intermediate contrast. This was interpreted as partial, 90 ° switching or evidence for “tail-to-tail” domain structure formation.